2022
DOI: 10.1155/2022/8997449
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Pesticide Residues in Water and Sediments from River Tano, Ghana

Abstract: Pollution due to pesticide residues has been reported in the downstream of the Tano Basin in the rainy season and has been attributed to the anthropogenic activities upstream. However, data on the seasonal variations in pesticide residues in the upstream of Tano Basin are limited. Seasonal variations in 13 organochlorine pesticide residues, 8 organophosphorus pesticide residues, and 5 synthetic pesticide residues in water and sediment samples of River Tano upstream were assessed through extraction and Varian C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…In addition, it also suggested their intensive use during the dry. This agrees with the study of Nyantaky et al [48].…”
Section: Discussionsupporting
confidence: 94%
“…In addition, it also suggested their intensive use during the dry. This agrees with the study of Nyantaky et al [48].…”
Section: Discussionsupporting
confidence: 94%
“…While some recorded higher mean values in the rainy season (Aldrin, Paraquat dichloride, Glyphosate, Imidachlopride, and λ-Cyhalothrin), others had higher mean values in the dry season. Because of the complex nature of factors that determine the seasonal pattern of pesticides in aquatic environments, different studies have obtained different seasonal trends, while some have reported higher mean values of pesticides during the rainy season (Harnpicharnchai et al, 2013;Stamatis et al, 2013;Jayasiri et al, 2022;Nyantakyi et al, 2022;), others have reported higher levels in dry season (Konstantinou et al, 2006;Cunha et al, 2022;Toth et al, 2022). The major factor is the seasons of pesticide application, which depends on the locality.…”
Section: Resultsmentioning
confidence: 99%
“…The major source of pesticide to surface water is runoff from agricultural land. Increased application leads to higher levels (Maloschik et al, 2007;Nyantakyi et al, 2022). A study by Pimentel (2003) showed that 99.9% of pesticides applied to agricultural targets end up in the environment.…”
Section: 𝐻𝐼 = ∑ 𝐻𝑄 (7)mentioning
confidence: 99%
“…However, only a small fraction of profenofos can be absorbed by pests, while most of the rest drifts to the environment and is often detected in agricultural water. For example, profenofos contaminations of up to 2.3 mg•L −1 were found in the Bubula River [5], and 0.074 ± 0.04 µg•L −1 and 0.303 ± 0.07 µg•L −1 in water of the Tano River during the rainy and drought seasons [6]. Profenofos has strong toxicity towards non-targeted organisms, including humans.…”
Section: Introductionmentioning
confidence: 99%